Inhibition of corrosion-driven organic coating delamination and filiform corrosion on iron by phenyl phosphonic acid - Geraint Williams (6th International Conference: Advances in Corrosion Protection by Organic Coatings, 2017)
In-coating phenyl phosphonic acid (H2PP) additions are investigated as inhibitors of corrosion-driven organic coating disbondment and anodic filiform corrosion (FFC) on iron surfaces. In-situ scanning Kelvin probe (SKP) experiments under atmospheric corrosion conditions are used to study the influence of the quantity of dissolved H2PP in the organic coating on the kinetics of cathodic delamination. It is demonstrated that, in a standard delamination investigation, increasing levels of H2PP progressively decrease the delamination rate up to 55%. In-coating H2PP additions are shown to be much more effective in a realistic scenario where electrolyte additions are made to a scribed defect and rates of cathodic disbondment are slowed by up to 99%. From the observed delamination kinetics, an inhibition mechanism is proposed whereby H2PP additions interact with the underlying iron to form an interfacial salt layer that blocks underfilm oxygen reduction. In terms of FFC inhibition, a threshold has been established whereby, with additions of 10% or below H2PP is shown to enhance the filament propagation rate due Cl− attack via an insufficient blocking layer. However, above 10% H2PP additions, propagation is slowed by up to 76%.